1999
DOI: 10.1164/ajrccm.160.1.9809041
|View full text |Cite
|
Sign up to set email alerts
|

Acute Purulent Exacerbation of Chronic Obstructive Pulmonary Disease andChlamydia pneumoniaeInfection

Abstract: In order to investigate the role of bacteria, including Mycoplasma pneumoniae and especially Chlamydia pneumoniae in acute purulent exacerbations of chronic obstructive pulmonary disease (COPD), we examined sputum specimens and acute and convalescent sera taken 26 d apart from 49 outpatients experiencing an acute purulent exacerbation of COPD. The sera were tested for antibodies to C. pneumoniae with the microimmunofluorescence test, and for antibodies to M. pneumoniae with the indirect fluorescence antibody t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 18 publications
3
57
0
11
Order By: Relevance
“…The term ''atypical pathogen'' most commonly refers to Mycoplasma pneumoniae, Chlamydia pneumoniae and Legionella pneumophila. AECOPD [7][8][9][10][11][12][13][14][15][16][17]. However, the interpretation of the role of these atypical pathogens in AECOPD is not easy, since these organisms are difficult to cultivate from respiratory tract specimens.…”
mentioning
confidence: 99%
“…The term ''atypical pathogen'' most commonly refers to Mycoplasma pneumoniae, Chlamydia pneumoniae and Legionella pneumophila. AECOPD [7][8][9][10][11][12][13][14][15][16][17]. However, the interpretation of the role of these atypical pathogens in AECOPD is not easy, since these organisms are difficult to cultivate from respiratory tract specimens.…”
mentioning
confidence: 99%
“…Since late 1970's, several authors suggested a relationship between COPD and M. pneumoniae infection [Buscho et al, 1978;Gump et al, 1976;Smith et al, 1980], but it was until late 1990's and early 2000's that several studies based on serology brought attention once more on this issue. [Lieberman et al, 2001[Lieberman et al, , 2002Mogulkoc et al, 1999]. It is well known that mycoplasmas species pathogenic for humans have the ability to induce chronic disease states in which clearance of the bacteria is extremely difficult.…”
Section: Role In Copd and Asthmamentioning
confidence: 99%
“…Based on IgG and IgM antibody titers, C. pneumoniae has been reported as an etiologic factor in 4 to 34% of AE-COPDs (87)(88)(89)(90)(91). Disparities in reported rates likely relate to differences in serologic methods used to identify C. pneumoniae infection and in the prevalence of infection reported in patients with stable COPD disease (92).…”
Section: Bacteriamentioning
confidence: 99%
“…Disparities in reported rates likely relate to differences in serologic methods used to identify C. pneumoniae infection and in the prevalence of infection reported in patients with stable COPD disease (92). By contrast, M. pneumoniae has been identified in only a minority (,1-14%) of AE-COPDs (71,89,93,94).…”
Section: Bacteriamentioning
confidence: 99%